2012
DOI: 10.1016/j.jneb.2011.03.143
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Mindful Restaurant Eating Intervention on Weight Management in Women

Abstract: Objective To evaluate the effect of a Mindful Restaurant Eating intervention on weight management. Design Random control trial. Setting Greater metropolitan area of Austin, Texas. Participants Women (n = 35) 40-59 years old who eat out at least 3 times per week. Intervention The intervention, using 6 weekly 2 hour small group sessions, focused on reducing calorie and fat intake when eating out through education, behavior change strategies, and mindful eating meditations. Main Outcome Measures Weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
107
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 27 publications
6
107
1
3
Order By: Relevance
“…The SEEBS has also been used in other studies in which the samples included Blacks (Nabi & Thomas, 2012;Timmerman & Brown, 2012) and emerging adults (Nabi & Thomas, 2012). Reliability was established using test-retest reliability.…”
Section: Reliabilitymentioning
confidence: 99%
“…The SEEBS has also been used in other studies in which the samples included Blacks (Nabi & Thomas, 2012;Timmerman & Brown, 2012) and emerging adults (Nabi & Thomas, 2012). Reliability was established using test-retest reliability.…”
Section: Reliabilitymentioning
confidence: 99%
“…A study conducted by Timmerman and Brown examined the effects of a mindfulness-based restaurant eating intervention in perimenopausal women and found that women in the mindfulness group ate less (45). Reviewers of 21 mindfulness-based interventions found that 86% of studies supported the notion that these interventions are efficacious in positively changing obesity-related eating behaviors (46).…”
Section: Mindfulness Strategiesmentioning
confidence: 99%
“…Results from this study show that participants in the mindfulness training group had significantly lower stress perceptions than those in the control group (50 and mindful eating tips such as chewing food thoroughly before swallowing, savoring the aroma and taste of food, and creating a pleasurable experience around food and eating which may include eating in a designated eating spot with minimal distractions (39,47). Within the realm of mindful eating meditations, there are those that are focused on breathing (49,104,105), awareness of the senses associated with eating in order to maximize enjoyment (45,47,51,108), relaxation (45), attention to internal hunger cues such as hunger and satiety (45,48,49,51,56,105), and identification of emotional and external eating triggers (49,56). The use of these strategies alone or in combination has been employed in many interventions investigating the effect of mindfulness-based strategies on eating behaviors.…”
Section: Mindfulnessmentioning
confidence: 99%
“…Next, would be the inclusion of mindfulness training in the behavioral modification process, which has been shown to improve weight loss, along with self monitoring. 163 Additionally, it has been shown that daily weight monitoring may lead to increased weight loss. Unpublished data from the VA's MOVE program has shown a 25% increase in weight loss with the institution of daily weights 164 and is further supported by recent research on weight self-monitoring.…”
mentioning
confidence: 99%